Morphological and Molecular Identification of Trichoderma Isolates Used as Biocontrol Agents by DNA Barcoding - Yüksel Gezgin; Gülce Güralp; Ayşe Berçin Barlas; Rengin Eltem (European Journal of Biology)
Objective: Trichoderma genus are environmentally friendly, targeted biocontrol agents used in organic agriculture. Currently, due to the increasing number of organic farming practices, Trichoderma species form a good market as commercial biocontrol agents. This study aims to make morphological and molecular identification of Trichoderma isolates, which were found to be potential biocontrol agents against plant pathogenic fungi, and to perform phylogenetic diversity analyses of these species using different bioinformatics tools. Materials and Methods: Two different gene regions (the nuclear ribosomal internal transcribed spacer (ITS) and translation elongation factor 1 (EF) were used for molecular identification of Trichoderma isolates in this study. Polymerase Chain Reaction (PCR) related regions were amplified and sequenced using primers specific to these gene regions. Following molecular identifications based on these two different gene regions, phylogenetic trees were drawn and polymorphic regions in the nucleotide sequences of these genes were determined. Results: As a result of the study, Trichoderma isolates were determined as T. citrinoviride Bissett and T. atroviride P. Karst. at the species level. This study not only provides essential information about the biodiversity of Trichoderma species, which is a biocontrol agent, but also allows the design of new species-specific primers based on the polymorphic regions of both species. Conclusion: It will be possible to make fast and low-cost molecular identification independent of sequence analysis by using primers unique to these species in the future.